Training Of Youth Health About Nutritional Status Of Youth and Early Detection Reproductive Health Problems Teenager In MAN 1 Banjarmasin Tahun 2021 - Muflihah; Ari Lestari, Nur Cahyani; Maulida, Hanifa (UrbanGreen Central Media, 2021)
The purpose of this service is to get an overview of the role of health cadres regarding the nutritional status of adolescents and early detection of adolescent reproductive health at MAN 1 Banjarmasin. This service uses a descriptive method with a quantitative random sampling approach and pretest and posttest methods. Test data using T-Test Paired Two Sample Test Parametric and Non Parametric. The results show persistence in implementing a balanced nutritional status and detecting adolescent health problems through adolescent health cadres with an accumulated pretest value of 3,380 and an increase in posttest value of 870 to 4,250. While the results of the T-Test Paired Two Sample, the average value of the pretest was 65.00 and the posttest was 81.73. The average score increases indicating that the training has been effective in changing the attitudes, behavior and knowledge of the students regarding the importance of nutritional status and early detection of adolescent reproductive health problems. The correlation value of 0.3912 indicates that the relationship between pre-test and post-test is quite strong.